SUBJEKTIVITAS DALAM PENAFSIRAN AL-QURAN: FENOMENA TAFSIR BERCORAK SEKTARIAN - Mawardi, Mawardi (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2018)
Tafseer was issued from the desire of mufaseer in revealing the content of Quran which aims to answer various problems of life. In this effort, some commentators forced the Quran to legitimize opinions and groups. In order for its purpose to be achieved, the mufaseer interpretate (taâwil) the verses in order to fit the groups and schools followed.